Patient‐incurred cost of inpatient treatment for Tuberculosis in rural Malawi. Issue 5 (28th February 2020) - Shin, Hyejeong; Ngwira, Lucky G.; Tucker, Austin; Chaisson, Richard E.; Corbett, Elizabeth L.; Dowdy, David W.
Abstract: Objectives: To mitigate the economic burden of tuberculosis (TB), it is important to fully understand the costs of TB treatment from the patient perspective. We therefore sought to quantify the patient‐incurred cost of TB treatment in rural Malawi, with specific focus on costs borne by patients requiring inpatient hospitalisation. Methods: We conducted a cross‐sectional survey of 197 inpatients and 156 outpatients being treated for TB in rural Malawi. We collected data on out‐of‐pocket costs and lost wages, including costs to guardians. Costs for inpatient TB treatment were estimated and compared to costs for outpatient TB treatment. We then explored the equity distribution of inpatient TB treatment cost using concentration curves. Results: Despite free government services, inpatients were estimated to incur a mean of 137 (standard deviation: 147) per initial TB episode, corresponding to >50% of annual household spending among patients in the lowest expenditure quintile. Non‐medical hospitalisation costs accounted for 88% of this total. Patients treated entirely as outpatients incurred estimated costs of 25 (standard deviation: 15) per episode. The concentration curves showed that, among individuals hospitalised for an initial TB episode, poorer patients shouldered a much greater proportion of inpatient TB treatment costs than wealthier ones (concentration index: −0.279). Conclusion: Patients hospitalised for TB in resource‐limited rural Malawi experience devastating costs of TB treatment. Earlier diagnosis and treatment must be prioritised if we are to meet goals of effective TB control, avoidance of catastrophic costs and provision of appropriate patient‐centred care in such settings. Abstract : Objectifs: Pour atténuer la charge économique de la tuberculose (TB), il est important de bien comprendre les coûts du traitement de la TB du point de vue du patient. Nous avons donc cherché à quantifier les coûts encourus par les patients pour le traitement de la TB dans les zones rurales du Malawi, en mettant l'accent sur les coûts supportés par les patients nécessitant une hospitalisation. Méthodes: Nous avons mené une enquête transversale auprès de 197 patients hospitalisés et 156 patients ambulatoires traités pour la TB dans les régions rurales du Malawi. Nous avons collecté des données sur les dépenses payées directement de la poche et les pertes de salaire, y compris les coûts pour les gardiens des malades. Les coûts du traitement anti‐TB des patients hospitaliser ont été estimés et comparés aux ceux des patients ambulatoires. Nous avons ensuite exploré la répartition des équités propres au coût du traitement de la TB des patients hospitalisés en utilisant des courbes de concentration. Résultats: Malgré les services gratuits du gouvernement, les patients hospitalisés encouraient en moyenne estimée de 137 (écart‐type: 147 ) par épisode initial de TB, ce qui correspond à >50% des dépenses annuelles des ménages chez les patients du quintile de dépenses le plus bas. Les frais d'hospitalisation non médicaux représentaient 88% de ce total. Les patients traités entièrement en ambulatoire encouraient des coûts estimés à 25 (écart type: 15 ) par épisode. Les courbes de concentration ont montré que, parmi les personnes hospitalisées pour un premier épisode de TB, les patients les plus pauvres supportaient une proportion beaucoup plus élevée des coûts de traitement de la TB en hospitalisation que les plus riches (indice de concentration: ‐0, 279). Conclusion: Les patients hospitalisés pour la TB dans les régions rurales pauvres du Malawi connaissent des coûts dévastateurs pour le traitement de la TB. Le diagnostic et le traitement précoces doivent être priorisés si nous voulons atteindre des objectifs de contrôle efficace de la TB, d'évitement des coûts catastrophiques et de prestation de soins appropriés centrés sur le patient dans de tels contextes .